An Assessment of Tropospheric Water Vapor Feedback Using Radiative Kernels. Issue 3 (3rd February 2018) - Liu, Run; Su, Hui; Liou, Kuo‐Nan; Jiang, Jonathan H.; Gu, Yu; Liu, Shaw Chen; Shiu, Chein‐Jung
Abstract: Water vapor feedbacks on different time scales are investigated using radiative kernels applied to the Atmospheric Infrared Sounder and Microwave Limb Sounder satellite observations, as well as the Coupled Model Intercomparison Project Phase 5 model simulation results. We show that the magnitude of short‐term global water vapor feedback based on observed interannual variations from 2004 to 2016 is 1.55 ± 0.23 W m −2  K −1, while model‐simulated results derived from the Coupled Model Intercomparison Project Phase 5 runs driven by observed sea surface temperature range from 0.99 to 1.75 W m −2  K −1, with a multimodel mean of 1.40 W m −2  K −1 . The long‐term water vapor feedbacks derived from the quadrupling of CO2 runs range from 1.47 to 2.03 W m −2  K −1, higher than the short‐term counterparts. The systematic difference between short‐term and long‐term water vapor feedbacks illustrates that care should be taken when inferring long‐term feedbacks from interannual variabilities. Also, the magnitudes of the short‐term and long‐term feedbacks are closely correlated ( R  = 0.66) across the models, implying that the observed short‐term water vapor feedback could be used to constrain the simulated long‐term water vapor feedback. Based on satellite observations, the inferred long‐term water vapor feedback is about 1.85 ± 0.32 W m −2  K −1 . Key Points: The short‐term water vapor feedback based on AIRS‐MLS observations from 2004 to 2016 is 1.55 ± 0.23 W m −2  K −1 The long‐term water vapor feedback inferred from observations is 1.85 ± 0.32 W m −2  K −1